2013
DOI: 10.1590/s0100-40422013000800005
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and removal of chromium from water by using moringa seed cake (Moringa oleifera Lam.)

Abstract: Recebido em 14/11/12; aceito em 13/5/13; publicado na web em 17/7/13 This study evaluated the adsorption capacity of chromium from contaminated aqueous solutions by using Moringa oleifera Lam. seeds. Parameters such as solution pH, adsorbent mass, contact time between solution and adsorbent, isotherms, thermodynamic, kinetics, and desorption were evaluated. The maximum adsorption capacity (Q m ) calculated to be 3.191 mg g −1 for the biosorbent. Activated carbon was used for comparison purposes in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 31 publications
(44 reference statements)
1
8
0
5
Order By: Relevance
“…10i-l). Meneghel et al (2013), Rubio et al (2013b), Coelho et al (2014) and Schwantes et al (2015) also found lower desorption rates for Cr 3+ , respectively, using the adsorbents: Moringa oleífera L., Crambe abyssina H., cashew nut shell, cassava peels in natura; all authors state the Cr is probably chemisorbed by the biomass. In most tests (Fig.…”
Section: Efficiency Of Adsorption and Desorptionmentioning
confidence: 92%
See 1 more Smart Citation
“…10i-l). Meneghel et al (2013), Rubio et al (2013b), Coelho et al (2014) and Schwantes et al (2015) also found lower desorption rates for Cr 3+ , respectively, using the adsorbents: Moringa oleífera L., Crambe abyssina H., cashew nut shell, cassava peels in natura; all authors state the Cr is probably chemisorbed by the biomass. In most tests (Fig.…”
Section: Efficiency Of Adsorption and Desorptionmentioning
confidence: 92%
“…(Gonçalves Jr. et al 2013b;Meneghel et al 2013), biomass of Jatropha (Jatropha curcas) (Nacke et al 2016), wheat straw , mussel shell, pinus ashes, oak ash, pinus bark and hemp residues (Quintans-Fondo et al 2016a, b, c). Although the economic benefits of nontransformation of biomass, studies are being carried out in order to increase the potential of biosorbents removal capacity, with the goal of giving new functional groups on the adsorbent surface through superficial chemical modifications on adsorbents mostly from vegetable origin (Wan Ngah and Hanafiah 2008;Schwantes et al 2015Schwantes et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…(MENEGHEL, 2013). Assim como determinado neste estudo, em seu trabalho usando casca de Moringa oleífera como biossorvente para a remoção de chumbo, determinou como tempo de contato para se atingir o equilíbrio na remoção de chumbo 30min, já para o uso da folha como biossorvente, sob as mesmas condições (pH 5, 25°C, 10 mg/L Pb 2+ e 0,4 g de adsorvente) o tempo de equilíbrio foi superior, em torno de 50min.A determinação do tempo de equilíbrio usando sementes de moringa, também foi avaliada para outros metais, dentre eles, o Cádmio e o Cromo, em estudos desenvolvidos por Sharma et al (2006) e Meneghel et al (2013), respectivamente, em que os tempos de equilíbrio foram superiores ao encontrado neste estudo. Para o cádmio, o tempo suficiente para que ocorresse o equilíbrio foi de 40 minutos para uma solução a 10mg/L adicionado de 2g de biossorvente, enquanto que para o cromo foi de 120 minutos utilizando-se uma solução com a mesma concentração, porém diferindo na quantidade de moringa, 400 mg.…”
Section: Avaliação Do Tempo De Equilíbrio E Do Percentual De Remoção unclassified
“…No Brasil, a princípio, a moringa foi introduzida para fins ornamentais e mais tarde veio a ser cultivada por sua importância medicinal e alto valor nutritivo, bem como por sua importância industrial devido as suas propriedades de coagulação, clarificação e adsorção em soluções aquosas na remoção de poluentes (MENEGHEL et al, 2013).…”
Section: Introductionunclassified
“…Dentre estes processos, a biossorção tem sido amplamente estudada para a remoção de vários compostos, incluindo os metais, visado o tratamento de águas e efluentes. [4][5][6][7] O processo de biossorção emprega como adsorvente materiais de origem natural o que o torna uma alternativa, economicamente atrativa, para tratamento de águas e efluentes. Entre as caracterís-ticas dos processos de tratamento por biossorção estão os baixos custos operacionais, minimização do volume de lodos químicos e/ ou biológicos, alta eficiência, tratamento de efluentes muito diluídos e não requer utilização de nutrientes adicionais durante o processo.…”
Section: Introductionunclassified